2008
DOI: 10.5007/2175-7925.2008v21n1p53
|View full text |Cite
|
Sign up to set email alerts
|

Análise faunística e flutuação populacional de cigarrinhas (Hemiptera, Cicadellidae) em pomar cítrico no município de Chapecó, Santa Catarina

Abstract: Visando caracterizar os ecossistemas de pomares cítricos da Região Oeste de Santa Catarina em relação às espécies de Cicadellidae, desenvolveu-se uma análise faunística em Chapecó. Para a caracterização do município foram medidos os índices de abundância, constância, dominância e freqüência das moscas das frutas. O levantamento foi feito utilizando-se armadilhas do tipo bandejas amarelas. Dilobopterus costalimai, Acrogonia citrina e Scopogonalia subolivacea foram as espécies mais abundantes, constantes, freqüe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
1
0
3
Order By: Relevance
“…The remaining species were rare or occasional in both orchards. Similar results have been obtained by studies in Brazil Nunes et al 2007;Menegatti et al 2008;Miranda et al 2009;Molina et al 2010), where Dilobopterus costalimai Young was the dominant species; but other research has shown B. xanthophis as the most abundant and frequent species on citrus (Yamamoto et al 2001;2002;Coelho et al 2008).…”
Section: Resultssupporting
confidence: 88%
“…The remaining species were rare or occasional in both orchards. Similar results have been obtained by studies in Brazil Nunes et al 2007;Menegatti et al 2008;Miranda et al 2009;Molina et al 2010), where Dilobopterus costalimai Young was the dominant species; but other research has shown B. xanthophis as the most abundant and frequent species on citrus (Yamamoto et al 2001;2002;Coelho et al 2008).…”
Section: Resultssupporting
confidence: 88%
“…Additionally, Xyphon reticulatum (Signoret, 1854) Previous records in Brazil. Amazonas (Manacapuru and Rio Preto da Eva) (Feitosa 2017); Bahia (Miranda et al 2009); Espírito Santo (Antunes et al 2015;Resende 2020), Minas Gerais (Froza 2017); Paraná (Molina et al 2006); Rio de Janeiro (Mejdalani et al 2009); Rio Grande do Sul (Ott et al 2006;Müller 2008;Ringenberg et al 2010;Paris et al 2013;Faprin et al 2014;Peruzo et al 2014;Schneider et al 2017); Santa Catarina (Menegatti et al 2008;Giacomelli et al 2022); São Paulo (Giustolin et al 2009;Froza 2017).…”
Section: Resultsmentioning
confidence: 99%
“…La mayoría de esas investigaciones se centraron en la subfamilia Cicadellinae, por su hábito alimenticio y por ser la más relevante en cuanto a la transmisión de X. fastidiosa (Lopes 1999, Yamamoto et al 2002, Dos Santos et al 2005, Molina et al 2006, Nunes et al 2007, Menegatti et al 2008, Miranda et al 2009.…”
Section: Xylella Fastidiosaunclassified
“…En Brasil, se llevaron a cabo diversos estudios acerca de las especies de auquenorrincos presentes en cultivos cítricos afectados por CVC y su fluctuación estacional (Yamamoto & Gravena 2000, Giustolin et al 2009, sin embargo, la mayoría de esas investigaciones se centraron en la subfamilia Cicadellinae por ser la más relevante en cuanto a la transmisión de X. fastidiosa (Lopes 1999, Yamamoto et al 2002, Dos Santos et al 2005, Molina et al 2006, Nunes et al 2007, Menegatti et al 2008, Miranda et al 2009.…”
Section: Buenos Aires 2%unclassified